Experimental and numerical determination of the chloride penetration in cracked mortar specimens. Issue 2 (7th February 2016) - Sosdean, Corina; Marsavina, Liviu; De Schutter, Geert
Abstract : The presence of cracks in reinforced concrete structures added to the chloride-induced steel corrosion is worldwide one of the major causes of deterioration of reinforced concrete structures, producing loss of structural strength and stability. This study deals with the influence of artificial cracks on chloride penetration in mortar specimens by presenting both the experimental and the numerical results. The experimental results were obtained using chloride penetration tests on mortar specimens of different sizes, with and without artificial cracks, subjected to chloride exposure. Numerical results were obtained using transient finite element analysis by simulating chloride mass diffusion. Comparisons between the results on chloride penetration concluded that the numerical ones obtained using the mass transfer modulus agrees fairly well with the experimental ones. In addition, the influence of certain crack parameters such as crack length, crack depth and also time exposure on chloride ingress was considered.